The generalized geometric uncertainty principle for spin 1/2 system - Umai, H.; Zainuddin, H.; Chan, K. T.; Said Husain, Sh. K. (Union of researchers of Macedonia, 2021)
Geometric Quantum Mechanics is a version of quantum theory that has been formulated in terms of Hamiltonian phase-space dynamics. The states in this framework belong to points in complex projective Hilbert space, the observables are real valued functions on the space, and the Hamiltonian flow is described by the Schrödinger equation. Besides, one has demonstrated that the stronger version of the uncertainty relation, namely the Robertson-Schrödinger uncertainty relation, may be stated using symplectic form and Riemannian metric. In this research, the generalized Robertson-Schrödinger uncertainty principle for spin ½ system has been constructed by considering the operators corresponding to arbitrary direction.